The Role of Diet in Functional Dyspepsia Management - Duboc, Henri; Latrache, Sofya; Nebunu, Nicoleta; Coffin, Benoit (Frontiers in Psychiatry, 2020)
Functional dyspepsia is a common functional gastrointestinal disease that is characterized by postprandial fullness, early satiation, epigastric pain and/or epigastric burning. Eating a meal is a key factor in the occurrence of symptoms during functional dyspepsia, and patients frequently request dietary advice that could relieve these symptoms. Eating behaviors, irregular meal patterns and moderate-to-fast eating rates are significantly associated with functional dyspepsia. The role of diet is complex; fat ingestion increases the occurrence of symptoms in dyspeptic patients, which might be affected by cognitive factors and palatability. Data concerning the role of carbohydrates are conflicting. Wheat may induce symptoms in patients with nonceliac gluten/wheat sensitivity, and gluten-free diets might be beneficial. Data concerning the role of FODMAPs (Fructo, Oligo, Di-, Monosaccharides, And Polyols) in functional dyspepsia are lacking; however, as there is a frequent overlap between functional dyspepsia and irritable bowel syndrome, a diet that is low in FODMAPs might be useful in relieving some symptoms. Data concerning alcohol are also conflicting. Adherence to a Mediterranean diet seems to be associated with a decrease in dyspepsia symptoms. Finally, data concerning diet modifications are conflicting, and the impact of diet modifications on symptom intensity or frequency has never been reported in randomized prospective studies. Common sense dietary recommendations, such as eating slowly and regularly, as well as decreasing the fat content of meals, can be provided in daily clinical practice.